The Business Environment Of Armenia: Women's Role And Significance In It - Hakobyan, Yevgenya; Markosyan, Anahit (ՀՀ ԳԱԱ ՏԻ)
Զարգացած գործարար միջավայրը տնտեսական և սոցիալական կայունության հիմնական երաշխիքներից մեկն է։ Այն երկրներում ապահովում է մակրոտնտեսական քաղաքականության արդյունավետ իրականացում և տնտեսության դիվերսիֆիկացման ներդաշնակեցում: Բարենպաստ գործարար միջավայրը հանդիսանում է տնտեսության հիմնական շարժիչ ուժը։ Развитая бизнес-среда – одна из главных гарантий экономической и социальной стабильности. Это обеспечивает эффективную реализацию макроэкономической политики и гармонизацию диверсификации экономики в странах. Благоприятная бизнес-среда – главная движущая сила экономики. The developed business environment is one of the main guarantees of economic and social stability. It ensures the effective implementation of macroeconomic policy and the harmonization of economic diversification in the country. A favorable business environment is one of the key driving forces of the economy. It is noteworthy that in recent years, the fight against gender inequality has grown significantly. By the way, it includes increasing women's involvement in various fields.
Keywords: Business environment